Factors affecting pupil size after dilatation: the Twin Eye Study. Issue 10 (1st October 2000) - Hammond, Christopher J; Snieder, Harold; Spector, Tim D; Gilbert, Clare E
Abstract : BACKGROUND/AIMS: Well dilated pupils make eye surgery easier. A classic twin study was established to examine the relative importance of genes and environment in the variance of pupil size after mydriasis, and to examine the effects of other factors such as age, iris colour, and refractive error. METHODS: 506 twin pairs, 226 monozygotic (MZ) and 280 dizygotic (DZ), aged 49–79 (mean age 62.2 years, SD 5.7) were examined. Dilated pupil size was measured using a standardised grid superimposed over digital retroillumination images taken 50–70 minutes after mydriasis using tropicamide 1% and phenylephrine 10%. Univariate maximum likelihood model fitting was used to estimate genetic and environmental variance components. RESULTS: Dilated pupil size was more highly correlated in MZ compared with DZ twins (intraclass correlation coefficients 0.82 and 0.39 respectively). A model specifying additive genetic and unique environmental factors showed the best fit to the data, yielding a heritability of 78–80%. Individual environmental factors explained 18–19% of the variance in this population. Age only accounted for 2–3% of the variance and refractive error and iris colour did not significantly contribute to the variance. CONCLUSIONS: Pupil size after mydriasis is largely genetically determined, with a heritability of up to 80%.